Reactions to adverse incidents in the health services on Twitter: a mixed methods study - Sarah Meaney; Leanne Cussen (Frontiers Media S.A., 2015)
Background: Participation in social networking is commonplace and social media is transforming both health and health related research. Of the various social media platforms, Twitter must be considered a platform for rapid and immediate communication. There has been considerable national and international media coverage reporting a number of adverse incidents in the Irish maternity services. The media coverage of these adverse incidents, most recently about a cluster of perinatal deaths, stimulated much public debate including debate online. Aim: Our study aimed to explore the Twitter status updates, and subsequent responses, relating to a number of perinatal deaths which occurred in a maternity unit with approximately 2,000 births per year. Method: As this study examined Twitter status updates in relation to reported perinatal death a mixed methods approach was adopted. Firstly, status updates in English were searched utilising the Twitter search function on its website. A search was undertaken on all public status updates from January 29th 2014 to March 31st 2014 relating to the perinatal deaths. Data were quantitatively analysed in order to assess the frequency of status updates, the demographic profiles of users and to ascertain the potential reach of the status updates. Secondly qualitative analysis was employed to generate themes from the content that twitter users shared publically. Results: From January 29th 2014 to March 31st 2014, 3,577 Twitter status updates from 1,276 profiles relating to the perinatal deaths were identified. Of these, 54.1% (n=1615) were tweets, 38.9% (n=1392) were retweets and 15.9% (n=570) were replies. Over one third of all updates (36.8%; n=1317) were from profiles which identified the user as either a media outlet or media personnel. One in 10 (11.8%; 424) status updates were by those who self-identified as a parent. Twitter was not utilised as a platform by any healthcare authority to release a statement in relation to the perinatal deaths. From the qualitative findings tweets indicated that the viewers were shocked and upset by the reported perinatal deaths. Tweeters branded the maternity unit as unsafe and questioned the governance of the entire maternity service. Conclusions: Twitter activity provides a useful insight into the public's attitudes to health related events. Our findings would suggest that during this period the public perception formed was that the Irish maternity services were unsafe. This study found that one third of all content generated on Twitter in relation to the perinatal deaths were by media outlets or personnel. This activity is suggestive of the influence the media have within digital spheres. The role of the media in influencing public opinion and in turn patient's decision making is well documented. Twitter was not utilised as a platform by any healthcare organisation or authority to release a statement to the public in relation to the perinatal deaths. Further study to identify how the clinical community could develop tools to utilise Twitter and other social media platforms to disseminate valid health information could be beneficial.